Persona Deixis in the Balinese Script Dialogue "Bogolan" by A. Wiyat S. Ardhi - A.A.I. Mas Trisnamayuni; I Nyoman Kadana; I Nyoman Sujaya (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This research aims to describe the use of personal pronouns in the Balinese language, referred to as persona deixis expressions, especially in a dialogue context. The data for this research was extracted from written sources consisting of books containing four script titles. The data collection process utilized literature review and observation methods, along with note-taking techniques. The analysis employed the matching and distribution method with direct element division and determinant element separation techniques. The results of the analysis are presented in descriptive form and tables. The findings of this study outline the three forms of persona deixis, namely first-person deixis, second-person deixis, and third-person deixis. Each deixis expression was analyzed based on its meaning and reference according to the context found in the dialogue. With the presence of diverse language levels in Balinese, this research also analyzes the factors influencing the language levels used in a dialogue.